The Influence Of Investment Decisions And Corporate Governance On Firm Value With Financial Performance As A Mediating Variable: A Study On Pharmaceutical Companies Listed On The Indonesia Stock Exchange - Avivah, Bertha Fernanda Nur; Saifi, Muhammad (Accounting Department,, 2025)
Purpose — This study examines the influence of investment decisions and corporate governance on firm value, with financial performance as a mediating variable. Design/methodology/approach — This research employs a quantitative approach and uses path analysis to examine data from pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) between 2017 and 2022. The sample was selected through purposive sampling, focusing on variables such as investment decisions (measured by the Price-Earnings Ratio), corporate governance (measured by ownership and board composition), financial performance (measured by ROA), and firm value (measured by Tobin's Q). Findings — The results indicate that investment decisions and corporate governance have significant direct effects on firm value, and their effects are mediated by financial performance. That highlights the interconnected roles of these factors in enhancing firm value. Practical implications — The findings emphasize the importance of strategic investment decisions and robust corporate governance mechanisms. For investors, the study underscores financial performance as a critical factor in evaluating firm value. Originality/value — This study contributes to the literature by providing empirical evidence on the mediating role of financial performance in the relationship between investment decisions, corporate governance, and firm value, specifically in the pharmaceutical sector during a volatile period (2017–2022). Paper type — Research Paper